2018
DOI: 10.17233/sosyoekonomi.2018.04.06
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Bank Stability: A Financial Statement Analysis of Turkish Banks

Abstract: This paper attempts a financial statement analysis of Turkish banks and explores the determinants of bank stability, as proxied by non-performing loans ratio, using annual data on 27 Turkish banks for the years 2007-2015. We employ dynamic panel data estimation techniques by using the system GMM estimation techniques. Our results indicate that the significant determinants of NPLs that are able to explain the credit risk of Turkish banks include return on assets (ROA), loans to asset ratio, inefficiency index, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Using a binary probit model with several internal and external variables, the industrial production index was found to impact the NPL ratio with statistical significance. Danisman (2018) explored the determinants of bank stability using Turkish bank data from 2007-2015. The study employed GMM estimation techniques and found that return on assets, loans to asset ratio, inefficiency index, non-interest income share and loans loss provision share can all explain NPLs.…”
Section: Theme 2: Z-score Applications As a Bank Stability Measurementioning
confidence: 99%
“…Using a binary probit model with several internal and external variables, the industrial production index was found to impact the NPL ratio with statistical significance. Danisman (2018) explored the determinants of bank stability using Turkish bank data from 2007-2015. The study employed GMM estimation techniques and found that return on assets, loans to asset ratio, inefficiency index, non-interest income share and loans loss provision share can all explain NPLs.…”
Section: Theme 2: Z-score Applications As a Bank Stability Measurementioning
confidence: 99%
“…Hardouvelis and Vaianos (2023) came to similar conclusions about the negative impact of the growth of non-performing assets on the performance of Greek banks. The emergence of problem loans in the corporate sector can be explained by the credit risk of Turkish banks, which leads to a decrease in return on assets (ROA), the share of non-interest income and an increase in the share of provisions for loan losses, Danishman (2018) believes. Akhryomushkin (2018), who has researched the problems of the bank corporate lending development in Kazakhstan, believes that big business in the country is almost entirely owned, firstly, by international corporations (oil and gas and mining), which receive direct financing from parent companies and do not need loans from local banks; or secondly, to the state, which attracts long money on international capital markets cheaper than their cost in domestic private banks, and can also redistribute raw excess in favor of larger public sector companies (Perminov, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results suggested that the inefficiency and asset size increase NPLs, whereas interest rate and growth rate of GDP and capital adequacy decrease NPLs. Danisman (2018) studied determinants of NPLs in Turkey and stated that profitability, capital adequacy and bank size affect adversely credit quality. Kjosevski, Petkovski and Naumovska (2019) focused on examining the effect of determinants of NPLs in North Macedonia.…”
Section: Literature Reviewmentioning
confidence: 99%